2013
DOI: 10.1007/s10620-012-2549-x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease and Systemic AA Amyloidosis

Abstract: AA amyloidosis remains a serious complication of both Crohn's disease and ulcerative colitis, and is characterized by proteinuric renal dysfunction that may resolve following suppression of inflammatory activity. Patient and graft survival are excellent in patients who undergo renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 23 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…SSA, or AA amyloidosis, has been reported as a complication of IBD and was first described in 1936 [ 14 ]. Further research has supported this association between the two conditions [ 10 - 12 , 14 - 16 ] and it has been reported that SSA is more frequently present in patients with CD than in those with UC [ 14 ]. The incidence of SSA associated with IBD in the United States is estimated at 0.9% in patients with CD and 0.07% in those with UC [ 10 ].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…SSA, or AA amyloidosis, has been reported as a complication of IBD and was first described in 1936 [ 14 ]. Further research has supported this association between the two conditions [ 10 - 12 , 14 - 16 ] and it has been reported that SSA is more frequently present in patients with CD than in those with UC [ 14 ]. The incidence of SSA associated with IBD in the United States is estimated at 0.9% in patients with CD and 0.07% in those with UC [ 10 ].…”
Section: Discussionmentioning
confidence: 88%
“…It has been hypothesized that the predominance of SSA in CD patients may be related to the more pronounced acute phase and a higher prevalence of suppurative features among these patients. Another study suggested that the incidence of amyloidosis secondary to CD is decreasing, probably in response to better and newer treatment methods including the use of biologic agents [ 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusions that vigorous treatment including anti-tumour necrosis factor (TNF)-a agents of Crohn's disease (CD) complicated by AA amyloidosis, reduce amyloid A production, were confirmed [22][23][24]. Long survival after kidney transplantation for end-stage renal disease was also confirmed [24]. However failure of anti-TNF-a therapy of secondary AAamyloidosis was reported.…”
Section: Control Of Aa Amyloidosis Complicating Crohn'smentioning
confidence: 96%
“…Renal amyloidosis is a rare but serious complication of IBD, and is associated with significant morbidity and even mortality burden [37]. Secondary amyloidosis, the predominant type of amyloidosis in patients with IBD, is characterised by extracellular deposition of serum amyloid A, an acute phase reactant protein in different parts of the kidneys, leading to proteinuria or renal insufficiency [38]. Deposition of amyloid in the glomeruli will usually lead to proteinuria and/or nephrotic syndrome, while interstitial amyloid accumulation will result in renal insufficiency [39].…”
Section: Amyloidosismentioning
confidence: 99%